THE PYROLYSIS OF HIGH-DENSITY POLYETHYLENE (HDPE) AND POLYPROPYLENE (PP) PLASTIC WASTE BLEND - Marwani, Marwani; Trifarizy, Muhammad David (Indonesian Journal of Engineering and Science, 2024)
Plastic waste is a growing problem that hurts the environment. The pyrolysis method converts plastic waste into alternative fuels to address this issue. This study aimed to investigate the impact of temperature on the characteristics of pyrolysis oil produced from a combination of High-Density Polyethylene (HDPE) and PolyPropylene (PP) plastic waste. The study focused on the resulting pyrolysis oil's volume, density, viscosity, and calorific value. The study results showed that the highest pyrolysis oil yield was obtained at 450ºC, with a volume of 350 ml. The density of the pyrolysis oil ranged from 670-790 kg/m3, while the viscosity ranged from 1.611-2.401 cP. The calorific value of the pyrolysis oil ranged from 7393.7584-8946.3759 cal/gr. The results demonstrate that the temperature significantly impacts the characteristics of the resulting pyrolysis oil. The study findings could be useful in optimizing the pyrolysis process to obtain high-quality oil from mixed plastic waste streams, thereby reducing plastic waste and providing an alternative energy source. The study highlights the potential for converting mixed plastic waste into alternative fuels through pyrolysis.